Perbandingan Metode Deep Learning dengan Model LSTM dan GRU untuk Prediksi Perubahan Iklim - Mustofa, Amin; Setiawan, Hendra (Forum Kerjasama Pendidikan Tinggi (FKPT), 2024)
Climate plays a critical role in determining the quality of life in Indonesia, which demands in-depth understanding through the Koppen climate classification and the latest technology. From agriculture to urban infrastructure, public health, to ecosystem sustainability, every aspect of our lives is affected by climate conditions. Deep Learning methods such as Long Short-Term Memory (LSTM) and Gated Recurrent Units (GRU) are used to predict time series data because of their adaptive ability in learning complex data patterns. The LSTM and GRU models were tested with 2010-2021 data using batch_size 64, epochs 150, optimizer adam, and showed high accuracy (<10%). LSTM recorded MAPE: Rainfall 5.50%, Humidity 7.60%, Temperature 4.36%, Sunlight 8.29%. GRU recorded MAPE: Rainfall 5.01%, Humidity 6.86%, Temperature 4.35%, Sunlight 8.28%. Predictions for 2028 show that the Special Region of Yogyakarta has a Tropical Monsoon (Am), Tropical Savannah (As) and Tropical Rain Forest (Af) climate. These climate changes have significant impacts: increased rainfall increases the risk of flooding, threatening infrastructure and lives, while the As climate reduces agricultural productivity and increases food insecurity. Changes in rainfall and temperature affect people's health, with high humidity increasing the risk of tropical diseases and high temperatures causing heat stress. Climate change in the Am type increases the risk of floods and landslides, while in the Af type it threatens tropical rainforest ecosystems.